Physic nut culture under irrigated system: An energy analysis - Frigo, Michelle Sato [UNESP]; Bueno, Osmar de Carvalho [UNESP]; Esperancini, Maura Seiko Tsuitsui [UNESP]; Frigo, Elisandro Pires [UNESP]; Klar, Antonio Evaldo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2008)
Due to gradual reduction of oil reserves, energy alternatives have been studies and one of them is biodiesel. Physic nut (Jatropha curcas L.) is a potential culture for biodiesel. However, there are very few studies on this culture as to its agricultural and energetic characteristics. Therefore, it is necessary to do research so that production techniques, energy use and sustainability be developed. The aim of this experiment was to analyze costs of different energy sources (renewable and non-renewable ones) from physic nut under drip irrigation in order to evaluate its long-term sustainability in relation to energy balance and use of non-renewable sources. The studied culture was from an area of NNE Minas Agro-Florestal Ltda, located in Janauba-MG, Brazil. Data from primary sources (collected in field through oral reports) and secondary ones (data from literature) were used. Ten operations have been pointed out: manual clearing of the area (cutting of banana trees and vegetation raking), mechanical griding, mechanical raking, manual seedling formation, manual preparation and seedling planting,, manual insecticide application, manual fungicide application, manual weed removal, drip irrigation and manual harvest. As a result, energy balance was 2,141.66 MJ ha-1, that is for each kilo of produced fruits or 12.80 MJ of total energy, 4.62 MJ corresponds to input of non-renewable energy (fossil fuel, oil, and lubricants). Energy efficiency was 2.77, that is, for each kilo of produced fruits or 12.80 MJ it is necessary to use 35.46 MJ of non-renewable energy input. Culture efficiency was 0.36, that is, for each produced12.80 MJ or one kilo of fruits it was necessary to use 35.67 MJ of biological, fossil and industrial sources (energy input). It was concluded that this studied agroecosystem is unsustainable in the long run because of its great use of non-renewable energy. Considering the purpose of that culture is the production of renewable fuel, it is incoherent to use a higher amount of non-renewable sources for its production than produced energy.
Análise energética do primeiro ano de cultivo do pinhão-manso em sistema irrigado por gotejamento
Keywords: Biofuel; Culture efficiency and sustainability; Energy balance; Energy efficiency; Non-renewable sources